2002
DOI: 10.1007/s10198-002-0113-x
|View full text |Cite
|
Sign up to set email alerts
|

Narcoleptic and schizophrenic hallucinations

Abstract: The differential diagnosis of narcolepsy versus schizophrenia is sometimes complicated by similar phenomenology, particularly when hallucinations predominate. REM sleep disturbances seem fundamental in the pathophysiology of narcolepsy, and REM sleep intrusions during periods of wakefulness are often associated with hallucinations also in healthy controls and in patients with other brain disorders including schizophrenia. This study used a semistructured interview to investigate different aspects of hallucinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…The only different characteristic of hallucinations was the frequency of unimodal hallucinations (higher in schizophrenia) and of hypnagogic/hypnopompic hallucinations (higher in narcolepsy). Our data are in line with previous evidence showing that the lifetime prevalence of hallucinations does not differ in schizophrenia and narcolepsy (90.5 and 75%, respectively, in this study and 81 and 80%, respectively, in a previous one [39]). The pathogenesis of hallucinations in narcolepsy is ascribed to a dissociated REM sleep phenomenon [40] for their frequent occurrence at the transition between wakefulness and REM sleep together with their association with sleep paralysis.…”
Section: Discussionsupporting
confidence: 82%
“…The only different characteristic of hallucinations was the frequency of unimodal hallucinations (higher in schizophrenia) and of hypnagogic/hypnopompic hallucinations (higher in narcolepsy). Our data are in line with previous evidence showing that the lifetime prevalence of hallucinations does not differ in schizophrenia and narcolepsy (90.5 and 75%, respectively, in this study and 81 and 80%, respectively, in a previous one [39]). The pathogenesis of hallucinations in narcolepsy is ascribed to a dissociated REM sleep phenomenon [40] for their frequent occurrence at the transition between wakefulness and REM sleep together with their association with sleep paralysis.…”
Section: Discussionsupporting
confidence: 82%
“…However, its frequency remains unknown, and results are highly variable between studies, ranging from 1% to 10% 3 6 7 8 9 . Due to some overlapping symptoms (e.g., hallucinations) and similar age of onset for both conditions, patients with schizophrenia may be misdiagnosed with narcolepsy, and patients with narcolepsy may be misdiagnosed with psychotic disorders 3 7 14 15 Most patients with narcolepsy have sleep and body posture-related hallucinations, mainly visual or multisensory, and rarely unimodal verbal-auditory or stereotypic 3 7 14 15 16 17 . We found hypnagogic hallucinations in 70% of patients at disease onset, as expected in adults with NT1 1 3 14 , and various auditory stereotypic hallucinations in all patients but one at time of psychotic episode.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between the core symptoms of psychosis and symptoms of narcolepsy have been elaborated elsewhere93 in a study comparing 148 narcolepsy patients, 21 schizophrenic patients, and 128 healthy subjects, which found that episodes of hallucination in narcolepsy were sleep-related and posture-related, and more likely to be visual and kinetic (83% and 71% in narcolepsy, respectively, compared with 29% and 5% in schizophrenia);93 the drawback of the study included discordant sample sizes for the groups, and the groups were also from different populations.…”
Section: Differential Diagnosesmentioning
confidence: 99%